Thin walled pottery; Augusta Emerita; Chronology - Macarena BUSTAMANTE ÁLVAREZ (Zephyrus, 2011)
In this paper we present new considerations about the “emeritenses” thin walled pottery above all its start date traditionally established in the reign of Emperor Tiberius. To reach the new chronological proposal we use two elements: the contexts of consumption and new production sites documented in the capital of Lusitania.